Soteriologi dalam Iman Kristen: Anugerah Keselamatan Melalui Karya Kristus - Nada Rusmelia; Mitra Fitria; Natalia Esviana; Sarmauli (Indo Publishing, 2025)
This journal article aims to explore the Christian doctrine of salvation (Soteriology) systematically, focusing on its meaning, humanity's need for it, its realization through Christ's work, and its contemporary application. The research problem centers on the fundamental human condition of sin, which severs the relationship with God and necessitates divine intervention for redemption. Employing a qualitative literature research method with a theological systematic approach, this study analyzes biblical texts and theological works from scholars such as Jonar T.H. Situmorang, Louis Berkhof, and others. The findings confirm that salvation is solely God's grace, granted through faith in Jesus Christ, not human effort. It is actualized through Christ's incarnation, sinless life, atoning death, resurrection, and ascension, comprehensively addressed in the Ordo Salutis. The study concludes that Soteriology is not merely a theoretical concept but has profound practical relevance, calling believers to a life of continual repentance, faith, and holiness, enabling them to be agents of reconciliation in a conflicted modern world. The implications of this study underscore the necessity of grounding Christian life and witness in the definitive and complete work of Christ.